ANALISIS KEMAMPUAN PEMECAHAN MASALAH DAN MINAT BELAJAR MATEMATIKA MATERI PERKALIAN PESERTA DIDIK KELAS III MI NURUL ULUM WONOSARI GRESIK - Lilis Rahmawati; Arissona Dia Indah Sari (Jurnal Al-Fatih, 2022)
This research was conducted at MI Nurul Ulum Wonosari with the subject of class teachers and 3rd grade students totaling 10 students. This study aims to analyze problem solving skills and interest in learning mathematics in multiplication material for third grade students at MI Nurul Ulum Wonosari. According to the result of interviews, the problem-solving ability of students is still relatively low, because they still cannot understand and solve story problems correctly. In addition, in the learning process the teacher has explained the material well, but the teacher has not taught them how to count multiplication in a simple and efficient way. Based on these problems, researchers will conduct reseach with qualitative methods, namely reasearch that aims to analyze the conditions that occur in the field, using descriptive methods. The tests carried out were by conducting interviews and distributing a number of test questions about problem solving and distributing questionnaires of interest in learning mathematics. After doing the research, it was found that the students mathematical problem solving abilities were in good category, and the result of the questionnaire distribution showed that students had a very high interest in learning mathematics.